UPAYA INDONESIA DALAM MENANGANI PENYELUNDUPAN NARKOBA MELALUI PERAIRAN ACEH - Anindita, Vanya; Darwis; Supriadi, Imam Fadhil Nugraha (Jurusan Ilmu Pemerintahan Universitas Palanfka Raya, 2024)
This research analyzes the efforts made by the Indonesian government in drug smuggling cases, especially in the maritime region of Aceh. This research will also further examine the various challenges faced by the Indonesian government in handling drug smuggling cases. These include Indonesia's lack of information technology capabilities that have not been able to compete with the technological advances used by organized criminal networks. The results of this study show that although Indonesia has cooperated with various regional and international organizations to obtain financial assistance for the implementation of rehabilitation for drug users and victims as well as support in the more innovative information technology sector, this has not shown significant results in reducing the number of smuggling cases that occur along Indonesian waters, especially in the Aceh region. In addition, the lack of awareness and active participation of the local community towards the destructive impact of illegal drug abuse is also an obstacle in realizing the future of Indonesia free from the threat of narcotics.